'Real‐life' experience of preapproval carfilzomib‐based therapy in myeloma – analysis of cardiac toxicity and predisposing factors. (21st September 2015) - Danhof, Sophia; Schreder, Martin; Rasche, Leo; Strifler, Susanne; Einsele, Hermann; Knop, Stefan
Abstract: Background: Carfilzomib, the second‐generation proteasome inhibitor, is still awaiting approval for the treatment of multiple myeloma in Europe. Results from clinical trials have demonstrated favorable efficacy in advanced disease but have opened an ongoing debate on cardiac complications related to carfilzomib treatment. 'Real‐life' data are scarce. Methods/Patients: At our institution, 22 patients were registered within the European Carfilzomib Access Program for treatment with carfilzomib, dexamethasone, and a third combination partner depending on patient characteristics and prior treatment. Patients had received a median of six previous lines of therapy, and most were refractory to bortezomib (77%) and immunomodulatory drugs (95%). Results: Overall response rate was 65% with a median progression‐free survival of 6.0 months and a median duration of response of 6.8 months. Median overall survival was 14.9 months. Grade 3/4 adverse events (AEs) occurred in 50% of patients with 23% experiencing left ventricular failure. The risk of cardiac AEs was markedly increased after previous radiotherapy of the thoracic spine and concomitant administration of doxorubicin. Conclusion: Carfilzomib‐based treatment is efficient in advanced multiple myeloma. In our 'real‐life' patients, we found considerable cardiotoxic effects in some cases, indicating a need for careful patient selection and close monitoring of the at‐risk population.